Multiple myeloma and monoclonal gammopathy of undetermined significance: importance of whole-body versus spinal MR imaging - Bäuerle, Tobias; Hillengaß, Jens; Fechtner, Kerstin; Zechmann, Christian; Grenacher, Lars; Möhler, Thomas; Heiß, Christiane; Wagner-Gund, Barbara; Neben, Kai; Kauczor, Hans-Ulrich; Goldschmidt, Hartmut; Delorme, Stefan (Radiology, 2009)
Purpose - - To examine if standard magnetic resonance (MR) imaging of the axial skeleton is sufficient for evaluation of patients with multiple myeloma (MM) or monoclonal gammopathy of undetermined significance (MGUS) or if whole-body MR is necessary. - - Materials and Methods - - A total of 100 untreated patients with MGUS (n = 27) or any stages of MM (n = 73) were examined with whole-body MR imaging and MR imaging of the axial skeleton. The study was approved by the institutional ethics committee, and written informed consent was given. Spinal pattern (“no diffuse involvement” or “diffuse involvement” as assessed from the signal intensity of the spinal bone marrow), serum parameters, and stage of disease were correlated with the probability of detecting extra-axial lesions with and without destruction of cortical bone by using a multiple logistic regression model. - - Results - - Of 100 patients, 39 had lesions in the axial skeleton and 37 had lesions in the extra-axial skeleton. Of the latter group, nine patients had no axial lesions and 13 patients had lesions that violated cortical bone, which implied an increased fracture risk. Because of the extraaxial location, lesions in these patients could be diagnosed with whole-body MR only. In addition, no single or combination of clinical factors observed (stage of disease, serum parameters, and spinal pattern) allowed investigators to identify patients with a significantly increased probability of having extra-axial lesions or lesions violating cortical bone. - - Conclusion - - Whole-body MR imaging has potential for use in the initial work-up of patients with MGUS or MM, since almost one-half of all observed lesions would have been missed by using spinal MR imaging only and clinical parameters could not exclude the presence of extra-axial lesions. - - © RSNA, 2009
Gesehen am 12.01.2022